The effect of sales promotion and hedonic shopping motivation on impulse buying behavior and the impact to customer loyalty in social commerce TikTok shop - Ibrahim, Maulana Malik; Ariyanti, Maya; Iskamto, Dedi (Global Academy of Business Studies, 2025)
Purpose: This study aimed to analyze the effects of sales promotion and hedonic shopping motivation on impulse buying behavior and its subsequent impact on customer loyalty among TikTok Shop fashion product buyers in Indonesia. This study seeks to understand how sales incentives and emotional shopping drives foster unplanned purchases that strengthen long-term customer relationships. Research Methodology: Quantitative method was used in this study with individual analysis units, and data collection was done through a questionnaire with a valid sample of 400 respondents. Data analysis techniques used the Structural Equation Model (SEM) and Partial Least Squares (PLS) using the SmartPLS 4.0 application. Results: The findings indicate that both sales promotion and hedonic shopping motivation significantly influence impulse buying behavior. In turn, impulse buying positively and significantly contributes to customer loyalty. Sales promotions also directly enhance loyalty, while hedonic motivation demonstrates both direct and indirect effects through impulse buying. The model achieved strong predictive relevance, with R ² values of 0.459 for impulse buying and 0.415 for customer loyalty. Conclusions: Sales promotions and hedonic motivations play crucial roles in shaping impulsive purchase tendencies, which increase customer loyalty. The TikTok Shop benefits from strategic promotions and the emotional appeal of shopping experiences to retain customers in a competitive social commerce landscape. Limitations: This study focused only on fashion product buyers within the TikTok Shop in Indonesia, limiting generalization to other product categories or platforms. Contribution: This study contributes to the e-commerce and consumer behavior literature by integrating hedonic and promotional factors with loyalty outcomes, offering managerial insights for optimizing digital marketing strategies.